Polyvinylidene fluoride membranes probed by electrochemical impedance spectroscopy. (8th June 2018) - Luo, Qi-Zhao; Huang, Qing; Chen, Zhe; Yao, Lei; Fu, Ping; Lin, Zhi-Dong
Abstract: Electrochemical impedance spectroscopy (EIS) has been applied to characterize the structure of polyvinylidene fluoride (PVDF) membranes. The characteristic frequency, which directly obtained from the original EIS data, was used to clarify the difference of the membranes' structures. The experimental data indicated the equivalence between the characteristic frequency and the membrane resistance fitted from the equivalent circuit. The results evidenced that the characteristic frequency obtained directly from original EIS data without any fitting calculation can be used for in situ characterizing a membrane instead of the membrane resistance.